A rare case of cavitary lung cancer complicated with mycotic pneumonia and bullous emphysema: A case report and review of the literature. Issue 47 (November 2017) - Lu, Cun-Tao; Zhang, Rui-Mei; Wang, Heng; Kong, Feng-Wei; Wu, Wen-Bin; Gong, Long-Bo; Zhang, Miao
Abstract: Rationale: The accurate diagnosis and staging of cavitary lung cancer is challenging but essential for the choice of therapy; therefore, the differential diagnosis of cystic pulmonary lesions needs to be elucidated. Patient concerns: A patient was admitted with multifocal thin-walled cystic lesions in chest computed tomography. Diagnoses: The patient had been diagnosed as heterogeneous bullous emphysema pathologically about 3 years ago. His diagnosis turned out to be metastatic cavitary lung cancer complicated with fungal pneumonia this time. Interventions: The patient underwent lung volume reduction surgery during his first hospitalization. Concurrent systemic chemotherapy and whole brain radiotherapy were administered after the diagnosis of cystic lung cancer. Outcomes: The patient was lost to follow-up after the chemoradiotherapy. Lessons: Cavitary lung cancer should always be kept in mind during differential diagnosis of pulmonary cystic lesions. Pathological diagnosis by biopsy and surgery could be considered to avoid delayed treatment of malignancy.